Morphological Description of Ocean-Collected Portunus sp. First Crab (Crustacea: Brachyura: Portunidae) from the Obhur Creek, Red Sea, Saudi Arabia - Austin, Anand; N.M. Naqoor, Nada (Journal of King Abdulaziz University: Marine Sciences, 2022)
Twenty-one specimens of Portunus sp. first crab were obtained from plankton samples collected from the Obhur Creek, Central Red Sea, Saudi Arabia. These specimens have been morphologically described herein. The setal patterns of the first crabs of the present specimens were compared with those of the first crabs of P. sanguinolentus. Presence of two to three rows of setae on the coxa of maxillule and coxa and basial of the first maxilliped are found in both the species of Portunus first crabs compared herein. These features seem to be taxonomically significant as these features are found in one of the other genera of Portunidae – Thalamita.